(untitled) (Journal of the College of Education for Women, 2019)
this research five grammatical terminology, and predicate and ascribed to it and added and genitive, examined scientific accuracy envisaged in placed and how they conform to the content then proposed five alternative terminology, and proved that this alternative terminology reflects more accurately the content of conventional terminology in Arabic grammar lesson, logical approach relies on analysis of morphological derivation of the term and its language, and recommended research to pursue critical studies in grammatical terminology, because such research has Significant impact in removing the grammatical ambiguity of some scholars, as well as instrumental in the development of methods of teaching Arabic grammar, to return to the relationship between lexical meaning of vocabulary and semantic meaning of the term than scientific article clearer when the world and learners alike.